2014
DOI: 10.1007/978-3-319-03632-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Link Between Aggregated Industrial Production and the Carbon Price

Abstract: :This chapter assesses the extent to which economic activity and the carbon price are linked. Carbon price drivers can be mainly related to energy and institutional variables. However, the influence of the macroeconomic environment shall not be undermined. Various approaches exist in the literature, which favor financial market variables over macroeconomic variables. Following a review of the state of the EU ETS, the main channel of transmission between the variation of macroeconomic activity and the carbon pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Secondly, some people study carbon prices from financial markets. Chevallier (2014) found that the carbon futures have the ability to predict the carbon spot price [5]. Aatola et al (2013) analyze the behavior of enterprises in the pursuit of profit maximization from the micro point of view in the carbon emissions market, the results show that there is a strong correlation between the carbon futures market and the spot market [3].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Secondly, some people study carbon prices from financial markets. Chevallier (2014) found that the carbon futures have the ability to predict the carbon spot price [5]. Aatola et al (2013) analyze the behavior of enterprises in the pursuit of profit maximization from the micro point of view in the carbon emissions market, the results show that there is a strong correlation between the carbon futures market and the spot market [3].…”
Section: Review Of the Literaturementioning
confidence: 99%